SOD1 Promotes Cell Proliferation and Metastasis in Non-small Cell Lung Cancer via an miR-409-3p/SOD1/SETDB1 Epigenetic Regulatory Feedforward Loop - Liu, Shilong; Li, Bin; Xu, Jianyu; Hu, Songliu; Zhan, Ning; Wang, Hong; Gao, Chunzi; Li, Jian; Xu, Xiangying (Frontiers in Cell and Developmental Biology, 2020)
Superoxide dismutase 1(SOD1) is a major antioxidant with oncogenic effects in many human cancers. Although SOD1 is overexpressed in various cancers, the clinical significance and functions of SOD1 in non-small cell lung cancer (NSCLC), particularly the epigenetic regulation of SOD1 in NSCLC carcinogenesis and progression have been less well investigated. In this study, we found that SOD1 expression was upregulated in NSCLC cell lines and tissues. Further, elevated SOD1 expression could promote NSCLC cell proliferation, invasion and migration. While inhibition of SOD1 expression induced NSCLC G1-phase cell cycle arrest and promoted apoptosis. In addition, miR-409-3p could repress SOD1 expression and significantly counteract its oncogenic activities. Bioinformatics analysis indicated that SET domain bifurcated histone lysine methyltransferase1 (SETDB1) was involved in the epigenetic regulation of miR-409-3p and SOD1 expression and functions in NSCLC cells. Identification of this miR-409-3p/SOD1/SETDB1 epigenetic regulatory feedforward loop may provide new insights into further understanding of NSCLC tumorigenesis and progression. Additionally, our results incicate that SOD1 may be a potential new therapeutic target for NSCLC treatment.